Chinese herbal retention enema combined with magnetic vibration magneto-electric therapy: a promising therapeutic strategy for chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) - Yang Xuan; Hao Zhang; Jintao Shi; Weihan Zhu; Jintao Fang; Qinyu Zhang; Qianya Zhou; Gang Chen; Yue Duan (Journal of Men's Health)
Background: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common urological condition characterized by complex etiology, high incidence and limited treatment options. Despite extensive research, its pathogenesis remains poorly understood and high-quality, effective therapies are lacking. Methods: This propensity score-matched study assessed 92 patients by evaluating symptom scores, complications, and prognostic outcomes using the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), International Prostate Symptom Score (IPSS), and Hospital Anxiety and Depression Scale (HADS), with patients stratified based on baseline characteristics for outcome comparison. Results: The total clinical effective rate was significantly higher in the combination therapy group (91.30%) compared to the control group (76.09%, p < 0.05); the treatment process was uneventful in both groups, and four weeks after treatment, the total NIH-CPSI score and its subscales were significantly lower in the combination therapy group (−17.24 (6.84) vs. −12.54 (7.18), p < 0.05), with a more pronounced reduction in the IPSS score (−6.70 (2.54) vs. −3.87 (2.03), p < 0.05) and superior improvements in both peak and average urine flow rates—especially the latter—while neither regimen produced a significant improvement in mood scores. Conclusions: The combination of Chinese herbal retention enema and magnetic vibration magneto-electric therapy is more effective than magnetic vibration magneto-electric therapy alone in alleviating the primary symptoms of CP/CPPS, suggesting significant potential for broader clinical application. Clinical Trial registration: This study was registered on itmctr.ccebtcm.org.cn. And the registration number is ITMCTR2024000191.